An Instructional Model for Enhancing EFL Learners' Speaking Proficiency - Syarifudin Syarifudin (EDULANGUE, 2019)
Due to the central role of speaking skill and its escalating demands of instruction in various levels of education in Indonesia, a myriad of teaching approaches and strategies have been applied to equip learners with the competences enabling the development of this skill. As a widespread approach to English language teaching (ELT), which gains its popularity within the context of EFL, Communicative Language Teaching (CLT) is geared towards learners’ communicative competence comprising of grammatical competence, discourse competence, sociolinguistic competence, and strategic competence as the underlying abilities of speaking proficiency. The development of these competences can be better facilitated when learning takes its place both in and outside classrooms as the latter provides potential promises for learners’ speaking proficiency development. For this reason, this paper presents learners’ challenges for learning speaking, the model activities in and outside classrooms, the importance of speaking instruction and the components of communicative competence and speaking proficiency.